Effect of multifaceted intervention promoting early switch from intravenous to oral acetaminophen for postoperative pain: controlled, prospective, before and after study. Issue 7274 (9th December 2000) - Ripouteau, Claire; Conort, Ornella; Lamas, Jean Paul; Auleley, Guy-Robert; Hazebroucq, Georges; Durieux, Pierre
Abstract: Problem Need to improve the efficiency of postoperative pain management by early switching from intravenous to oral acetaminophen. Design Implementation of local guidelines aimed at improving nurses' and doctors' behaviour. A controlled, prospective, before and after study evaluated its impact on appropriateness and costs. Background and setting Orthopaedic surgery department (intervention) and all other surgical departments (control) of a university hospital. Five anaesthetists and 30 nurses of orthopaedic department participated in study. Key measures for improvement Reducing number of acetaminophen injections per patient, reducing consumption of acetaminophen injections; cost savings over a one year period. Strategies for improvement Multifaceted intervention included a local consensus process, short educational presentation, poster displayed in all nurses' offices, and feedback of practices six months after implementation of guidelines. Effects of change Mean number of acetaminophen injections per patient decreased from 6.81 before intervention to 2.36 six months after. Monthly consumption of acetaminophen injections per 100 patients decreased by 320.9 (95% confidence interval 192.4 to 449.4) in intervention department and remained unchanged in control departments. Annual cost reduction was projected to be £15 100. Lessons learnt Simple and locally implemented guidelines can improve practices and cut costs. Educational interventions can improve professionals' behaviour when they are based on actual working practices, use interactive techniques such as discussion groups, and are associated with other effective implementation strategies.